Financing Management in Private Junior High Schools: A Systematic Literature Review for Digital and Innovation Contexts - Chairun Nisa Male; Oki Dermawan (re-JIEM (Research Journal of Islamic Education Management), 2026)
Managing educational financing in private schools is a strategic aspect of ensuring institutional sustainability and the quality of educational services. The complexity of relatively autonomous funding structures requires financial governance that is transparent, accountable, and sustainability-oriented. This article analyzes concepts, models, and practices of financing management in private Junior High Schools using a Systematic Literature Review approach. The reviewed literature is limited to publications from the last ten years and is analyzed through content analysis techniques to identify patterns, trends, and research gaps. The review indicates a shift from an administrative approach toward a strategic, school-governance-based approach that integrates program planning with budgeting, internal oversight, and stakeholder participation. The effectiveness of financing management is influenced by needs-based planning, diversification of funding sources, digitization of reporting systems, and the principal’s managerial capacity. The main challenges include dependence on student fees and limited human resources for financial administrative management. Therefore, financing management in private junior high schools should be positioned as a strategic instrument to support organizational stability and the continuous improvement of educational quality.